A Sociological Model of Health Lifestyles - Cockerham, William C; Rütten, Alfred; Abel, Thomas (Croatian Medical Journal, 1996)
Aim. Formulation of a sociological model of health lifestyles to serve as a guide for future research. Method. Review of contributions of Weber (early century), Bourdieu (mid-century), and Giddens (late century) to lifestyle theory and assessment of relevant empirical studies. Results. Elements (socioeconomic, sociobiological, sociocultural, and sociopsychological) comprise dimensions (life chances, life conditions, life forms, and life sense) that influence choices (conduct) through a health habitus that results in patterns (lifestyles). Correspondence analysis is discussed as a method to explore the tendency of lifestyle practices to cluster in particular patterns and test the model. Conclusion. A sociological model which can be verified empirically is suggested as an initial step in developing a health lifestyle theory.
UnivIS-Import:2015-03-05:Pub.1996.phil.dps.iss.lsw.asocio
Keywords: Health; Life style; Sociological model